The Concept of Thayyib in A Review of the Quran and Science: Consumer Selection Over Quality Food - Syarifah, Umaiyatus; Holil, Kholifah; Resmisari, Ruri Siti; Rahmah, Azizatur; Griana, Tias Pramesti (Institut Agama Islam Negeri (IAIN) Curup, 2024)
Consumer selection of quality food ingredients is an important part in determining the thayyib of food. This is not without reason considering that only quality food with the right quantity can support health. Therefore we need food that is safe for consumption, therefore choosing the right food is the focus that must be considered. Islam regulates this both normatively and operationally. This paper tries to review the thayyib narrations explained in the Koran which are then related to science. The method used in this study is thematic interpretation using a scientific approach. The results of the study show that the word thayyib does not only mean good and useful but is also selective in choosing the right food, whether it is to be consumed in the form of food that has been served or in the form of food ingredients.